Extrasynaptic exocytosis and its mechanisms: a source of molecules mediating volume transmission in the nervous system - Trueta, Citlali; De-Miguel, Francisco F. (Frontiers in Physiology, 2012)
We review the evidence of exocytosis from extrasynaptic sites in the soma, dendrites and axonal varicosities of central and peripheral neurons of vertebrates and invertebrates, and how it may contribute to signaling in the nervous system. The finding of secretory vesicles in extrasynaptic sites of neurons, the presence of transmitters in the extracellular space outside synaptic clefts, and the mismatch between exocytosis sites and the location of receptors for these molecules in neurons and glial cells, have long suggested that in addition to synaptic communication, transmitters are released and act extrasynaptically. The catalog of these molecules includes low molecular weight transmitters such as monoamines, acetylcholine, glutamate, GABA, ATP, and a list of peptides including substance P, BDNF, and oxytocin. By comparing the mechanisms of extrasynaptic exocytosis of different molecules in various neuron types we show that extrasynaptic exocytosis is a widespread mechanism for communication in the nervous system that uses certain common mechanisms, which are different from those of synaptic exocytosis but similar to those of exocytosis from excitable endocrine cells. Somatic exocytosis, which has been measured directly in different neuron types, starts after high-frequency electrical activity or long experimental depolarizations and may continue for several minutes after the end of stimulation. Activation of L-type calcium channels, calcium release from intracellular stores and vesicle transport couples excitation and exocytosis from small clear or large dense core vesicles in release sites lacking postsynaptic counterparts. The presence of synaptic and extrasynaptic exocytosis endows individual neurons with a wide variety of time- and space-dependent communication possibilities. Extrasynaptic exocytosis may be the major source of signaling molecules producing volume transmission and by doing so may be part of a long duration signaling mode in the nervous system.